Weather and income: Lessons from the main European regions - David García-León (Fondazione Eni Enrico Mattei (FEEM), 2015)
Some recent papers by Dell et al. (2009) and Dell et al. (2012) (DJO) relating weather and economic outcomes, have delivered meaningful messages with clear implications to the effects of a changing climate. In a nutshell, the authors claim that a 1êC increase in global average temperatures would harm both the level and growth capacities of relatively poor countries, leaving rich countries basically unaffected. In this study, we make use of a detailed weather and economic dataset covering the main regions of the five largest economies in the Euro area in an attempt to refute the previous affirmation. In particular, we find in our sample that global warming affects, although in a modest manner, all regions within well-developed countries in the long-term (level effect). As in DJO, the level effect in poor regions is exacerbated. The latter regions also suffer from a slight negative short-term effect (growth effect). We claim also that the larger short-time response of these regions to a climate shock is partially adapted in the long-run.
Keywords: O1; O4; Q51; Q54; Q59; R11; 330; Economic Growth; Weather; Ricardian Analysis; Developed Economies; Climate Change; Adaptation; NUTS